Improvement of Quranic Reading Skills and Islamic Insight among Children and Adolescents in Tarai Bangun Village: a Participatory Action Research Approach - Suhendri Suhendri; Sopian Sinaga; Ahmad Zaky (ASSUNNAH PRESS, 2023)
This paper discusses the implementation of the Thematic Community Service Learning (KKN-T) program in Tarai Bangun Village, Tambang Sub-district, Kampar Regency, with the background of selecting a theme focusing on the need for religious and Islamic education in the village. The chosen theme for the KKN-T program is